Breeding for quantitative traits in plants - Bernardo, Rex Novero, 1965- (Stemma Press, 2020)
"Most of the economically-important traits in crops are quantitative and are controlled by many genes. Breeding for Quantitative Traits in Plants investigates the application of quantitative genetics to plant breeding. This book is an ideal text for a graduate-level course and a useful reference for practicing plant breeders"--